Routledge handbook of planning and management of global strategic infrastructure projects - Ochieng, Edward; Zuofa, Tarila; Badi, Sulafa (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines complex challenges in managing major strategic economic and social infrastructure projects"--
OCLC-licensed vendor bibliographic record.
Keywords: Infrastructure (Economics) -- Planning; Infrastructure (Economics) -- Management; TECHNOLOGY / Engineering / Civil; BUSINESS & ECONOMICS / Project Management